KARAKTERISASI SIFAT FISIKOKIMIA PATI UBI JALAR ORANYE (Ipomoea batatas, L.) SERTA PENGGUNAANNYA SEBAGAI KOMPOSIT EDIBLE FILM DENGAN PENAMBAHAN ZEIN PROTEIN - , TRI AGUNG WIDYARIZKI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Utilization of starch as edible film component has been developed. However, the research about edible film made from orange sweet potato starch has never been done. The purpose of this study was to determine the physicochemical properties of orange sweet potato starch and edible film characteristics with the addition of zein protein and glycerol. In this study, the starch of orange sweet potato were extracted by water, then precipitated, dried, and milled. Edible film were prepared by using casting method with a variation of the concentration of starch 1%, 1.5%, and 2% (w/v), with the addition of zein and plasticizer glycerol fixed concentration at 2% (w/w) and 30% (w/w) starch. The results showed that starch has 12,81% of water, 0,30% of ash content, 0,30% of protein, 0,82% of fat, and 85,78% of carbohydrate (by difference). Starch gelatinization time is 20,5 minutes and the temperature range 75-800C. The reducing sugar was detected in the starch which have been hydrolysed with acid. FTIR testing showed an identical group when compared with the commercial starch. Based on the test results, the orange sweet potato starch can be used as an edible film forming material. The higher starch concentration will increase the thickness and tensile strength characteristics, while solubility in water, elongation percentage and water vapor permeability were decreased in the physical properties and barrier properties of edible film. In the highest concentration of orange sweet potato starch used 2% (w/v), produced edible film with the thickness is 0,08 mm, the tensile strength is 4,2 MPa, the solubility is 20,7%, the percentage elongation is 33,7%, and water vapor permeability is 0,53 g.mm/m2.hours.kPa.